Analisa Rugi-Rugi Daya Pada Saluran Transmisi Tegangan Tinggi 150kv Pada Gardu Induk Jajar - Gondangrejo - kosasih, ghofur barum; , Umar, S.T., M.T (2017)
Over time, The development of energy rapidly. Electric Energy needs increasingly, require the availability of electrical energy efficient and quality. PT.PLN ( Persero ) have three levels in distribute electric power among other level generation, the level of transmitting and the distribution, so cause many to be a problem in it. The transmitting and distribution of there arelose out resources in cause by several factors. Losses power that occurs in the channel transmitting very need in note, because it could lead to the loss of the big enough.Analysis of the calculations lose out power carried on the system transmitting high strain 150 kv on gardu induk jajar to gardu induk gondangrejo. Analysis done with through the survey at the site and then do calculation losses power for a month in manual. Methods used the researchers do take data of Strain and the flows that in do every day. Take data done steadily for a month, at 10:00 and 19.00 pm. The conductor on the transmitting gardu induk jajar to gardu induk gondangrejo with type ACSR who have dimensions 240/40. The results of the conclusion analysis losses power is the highest losses that occurs during the day is on November 23, losses reached 1,035619 MW and at night, going on November 21 with losses greater than during the day that 1,398591 MW. In this research the number of losses in November 2016 reached 291259,728 kWh and PT.PLN ( persero ) get a loss of Rp328.025.443,00